A riverine biodiversity hotspot in northern Myanmar supports three new and narrowly endemic freshwater mussel species. Issue 9 (14th June 2022) - Bolotov, Ivan N.; Konopleva, Ekaterina S.; Chan, Nyein; Lunn, Zau; Win, Than; Gofarov, Mikhail Y.; Kondakov, Alexander V.; Tomilova, Alena A.; Vikhrev, Ilya V.
Abstract: The Western Indochina Subregion (Myanmar) represents a freshwater biodiversity hotspot of worldwide significance and houses a plethora of endemic freshwater species, among which are amphibians, fish, and various aquatic invertebrates. The freshwater mussel (Bivalvia: Unionidae) fauna of western Indochina is characterized by high taxonomic richness, with almost all species and several genera being endemic to the subregion. Furthermore, there are a number of species endemic to a single basin or even to a single tributary of a larger river system (the so‐called intra‐basin endemic taxa). Here, the discovery of three new, narrowly endemic freshwater mussel species from northern Myanmar is presented: Radiatula kachinensis sp. nov., Trapezidens mogaungensis sp. nov. (upper Ayeyarwady basin), and Lamellidens chindwinensis sp. nov. (upper Chindwin basin). All the new species are upland river specialists, which are under high human pressure as a result of habitat degradation, deforestation, oil palm expansion, river damming, and biological invasions. A nearly complete lack of data on the life cycles and fish hosts should be considered the most striking gap in recent knowledge of tropical Asian freshwater mussels. Here, available data on 27 species belonging to the genera Radiatula, Trapezidens, and Lamellidens are revised. It is shown that certain fish hosts are known for two species only. Further spread of the alien Chinese pond mussels ( Sinanodonta woodiana species complex) in Indochina may be considered one of the significant threats to native freshwater mussel populations. Here, it is shown that the temperate invasive lineage of S. woodiana is established in at least three non‐native populations in the Ayeyarwady and Salween basins. Moreover, the first arrival of the tropical invasive lineage of S. woodiana to Myanmar is announced, although it has been predicted previously. This lineage was found at two sites on the Shan Plateau (Ayeyarwady basin) close to the Chinese border.